Conservation Subdivision: Construction Phase – Native Landscaping Palette - Mark Hostetler; Martin B. Main (EDIS)
WEC284, a 9-page illustrated fact sheet by Mark Hostetler and Martin B. Main, discusses the importance of emphasizing native plants when selecting a landscape palette. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, May 2010.